(untitled) (Journal of Environmental Science and Natural Resources, 2015)
Health and wellbeing of women and children especially on maternal and neonatal health has long been a common goal throughout the world. Understanding the status of maternal and child health care for our country can provide us the valuable information regarding the impact of enriching health policies. Various types of annual reports, journals and published materials on maternal and child health and its regulatory factors with overall health status were collected and analyzed to finalize these articles. The findings of reviewing article was that on annual basis 75.6% of the children born in without the supervision of trained health service providers and 38.96% death occurrence for perinatal asphyxia due to below level neonatal health circumstances. Child mortality rate under 5 years old is 66 per 1000 in rural areas and the slum areas the rate above 90%. The coverage of the vaccine program has also improved (99%) substantially. The result also showed that sanitation and safe drinking water situation has improved than previous decades. The review report revealed that some of the problems are still remaining in the health sector to achieve the MDG, though we made great strides in improving the health of its population, much more than a countrys development situations. Inequities in access to health care, lack of meaningful participation of citizens in the health care system and the absence of effective accountability mechanisms has been found as a main health barriers. Finally, the progress of health care system has worked much, the government should support funding and logistic to continue and promote the enhancement of overall health care system in Bangladesh. DOI: http://dx.doi.org/10.3329/jesnr.v7i1.22171 J. Environ. Sci. & Natural Resources, 7(1): 197-206 2014